Length-weight relationship and condition factor of Nile tilapia (Oreochromis niloticus) fed diets supplemented with guava and star gooseberry leaf extract [version 2; peer review: 2 approved] - Nopadon Pirarat; Kim D. Thompson; Seema Vijay Medhe; Balasaheb Ramdas Chavan; Manoj Tukaram Kamble; Krishna Rugmini Salin (F1000Research)
Background Nile tilapia (Oreochromis niloticus) is predominant cultured species in aquaculture. However, there is a scarcity of literature regarding relationship between guava and star gooseberry leaf extract and the condition factor. Thus, the present study aims to investigate the effect of guava and star gooseberry leaf extract-supplemented diets on the specific growth rate, length-weight relationship, and condition factor of Nile tilapia. Methods Six hundred and thirty Nile tilapia (8.7±0.4 g) were randomly distributed among twenty-one tanks (30 fish per tank) within a recirculation system. Over a 60-day period, the fish were fed diets supplemented with 5g/Kg and 10g/Kg of guava leaf extract (GLE-5, GLE-10), star gooseberry leaf extract (SGLE-5, SGLE-10), and a mixture of both (MxLE-5, MXLE-10). Subsequently, specific growth rate, length-weight relationship, and condition factor were determined. Results After 60 days, the specific growth rate was significantly higher in all the GLE, SGLE, and MxLE groups compared to the control group. The final lengths and weights differed significantly both in the control group and all the GLE, SGLE, and MxLE groups. The analysis of the regression equation indicated a positive correlation (r = 0.970, 0.977, 0.976, 0.974, 0.974, 0.974, and 0.969) between the length and weight of Nile tilapia in the control group and in all the GLE, SGLE, and MxLE groups. The regression exponent “b” values in all the GLE, SGLE, and MxLE groups were >3, indicating a positive allometric growth pattern in Nile tilapia compared to the control (b=2.866), which exhibited a negative allometry. The final condition factor values did not differ significantly in either the control group or any of the plant extract groups. Conclusions Nile tilapia exhibited positive allometric growth patterns and maintained good health when fed with GLE, SGLE, and MxLE groups. Therefore, these plant extracts demonstrate suitability for commercial Nile tilapia production.